Separation of Low- Versus High-grade Crohn's Disease-associated Small Bowel Carcinomas is Improved by Invasive Front Prognostic Marker Analysis. (16th August 2019) - Arpa, Giovanni; Grillo, Federica; Giuffrida, Paolo; Nesi, Gabriella; Klersy, Catherine; Mescoli, Claudia; Lenti, Marco Vincenzo; Lobascio, Gessica; Martino, Michele; Latella, Giovanni; Malvi, Deborah; Macciomei, Maria Cristina; et al.
Abstract: Background and Aims: Crohn's disease-associated small bowel carcinoma is a rare event, usually reported to have a severe prognosis. However, in previous investigations we have found a minority of cases displaying a relatively favourable behaviour, thus outlining the need to improve the histopathological prediction of Crohn's disease-associated small bowel carcinoma prognosis. Methods: As in recent studies on colorectal cancer, a substantial improvement in prognostic evaluations has been provided by the histological analysis of the tumour invasive front; we therefore systematically analysed the tumour budding and poorly differentiated clusters in the invasive front of 47 Crohn's disease-associated small bowel carcinomas collected through the Small Bowel Cancer Italian Consortium. Results: Both tumour budding and poorly differentiated cluster analyses proved highly effective in prognostic evaluation of Crohn's disease-associated small bowel carcinomas. In addition, they retained prognostic value when combined with two other parameters, i.e. glandular histology and stage I/II, both known to predict a relatively favourable small bowel carcinoma behaviour. In particular, association of tumour budding and poorly differentiated clusters in a combined invasive front score allowed identification of a minor subset of cancers [12/47, 25%] characterised by combined invasive front low grade coupled with a glandular histology and a low stage [I or II] and showing no cancer-related death during a median follow-up of 73.5 months. Conclusions: The improved distinction of lower- from higher-grade Crohn's disease-associated small bowel carcinomas provided by invasive front analysis should be of potential help in choosing appropriate therapy for these rare and frequently ominous neoplasms.